2008
DOI: 10.1002/bit.21947
|View full text |Cite
|
Sign up to set email alerts
|

A high‐throughput screen for hyaluronic acid accumulation in recombinant Escherichia coli transformed by libraries of engineered sigma factors

Abstract: Hyaluronic acid (HA) is an important biomaterial with functional medical and cosmetic applications. As its synthesis has been recently reported in recombinant bacteria, it is of interest to develop a high throughput screening method for the rapid isolation of HA accumulating strains transformed by combinatorial libraries. Here we report a novel two-step screening strategy to select for better HA-producing recombinant Escherichia coli strains transformed by mutation libraries of rpoD and rpoS, coding for the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 37 publications
2
45
1
2
Order By: Relevance
“…During our studies of HA production, rpoA mutants showed up to ϳ60% improvement in titer (Fig. 4) compared to ϳ40% in the case of rpoD as measured by the same method (48). Despite these results, we do not believe that this constitutes sufficient evidence for favoring one target or the other; instead, we have argued that a better measure of the usefulness of a library is related to the a priori probability of finding improved mutants (22), not to whether a particular target delivers a phenotype of interest or not.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…During our studies of HA production, rpoA mutants showed up to ϳ60% improvement in titer (Fig. 4) compared to ϳ40% in the case of rpoD as measured by the same method (48). Despite these results, we do not believe that this constitutes sufficient evidence for favoring one target or the other; instead, we have argued that a better measure of the usefulness of a library is related to the a priori probability of finding improved mutants (22), not to whether a particular target delivers a phenotype of interest or not.…”
Section: Discussionmentioning
confidence: 62%
“…Using a previously reported high-throughput screening platform (48), we were able to screen an rpoA library and isolate several improved rpoA mutants. Figure 5 shows the HA concentrations relative to the control, quantified using the alcian blue method as described previously (48). It is clear from these results that significant phenotypic diversity was generated through the introduction of the rpoA library.…”
Section: Butanol Tolerance (I) Isolation Of a Mutant With Improved Gmentioning
confidence: 80%
See 2 more Smart Citations
“…It is suspected that a cascade of other sigma factors, pleiotropic regulators and pathway-specific regulators, might be triggered to express by σ hrdB (32). Engineering the binding factors of RNA polymerase has been successfully applied in the improvement of ethanol tolerance and productivity in Saccharomyces cerevisiae (33), and in the yield improvement of products expressed in the heterogeneous host E. coli (34,35). By binding to and affecting the promoter specificity of the RNA polymerase core enzyme, σ hrdB directs the selective transcription of gene sets and acts cooperatively with one or more Streptomyces extracytoplasmic function sigma factors to exert its control on downstream targets.…”
Section: Discussionmentioning
confidence: 99%